2020
DOI: 10.1037/hea0000863
|View full text |Cite
|
Sign up to set email alerts
|

Reducing exposure to ultraviolet radiation from the sun and indoor tanning: A meta-analysis.

Abstract: Objective: Skin cancer is the most frequently diagnosed cancer and rates are increasing because of global warming. This article reports a meta-analysis of randomized controlled trials of behavioral interventions to reduce exposure to ultraviolet radiation (UVR). The review aimed to (a) quantify the magnitude of intervention effects on indoor tanning, sun exposure, and sunscreen use, and (b) determine which intervention strategies maximize behavior change. Method: Out of 17,437 records identified via literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…8,9 It is challenging to assess the protective effect of each method of UVR protection separately in complex interventions consisting of several methods, and quantitative and objective approaches are scarce. 13 The minimal erythema dose (MED) is often used as a biological measure of UVR exposure and indicator of individual sensitivity to UVR. 14,15 However, the use of visual assessment of erythemal status (ie MED) as a way to estimate UVR exposure has several disadvantages: firstly, it is a subjective and simply phenomenological end point, reflecting acute inflammation with poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It is challenging to assess the protective effect of each method of UVR protection separately in complex interventions consisting of several methods, and quantitative and objective approaches are scarce. 13 The minimal erythema dose (MED) is often used as a biological measure of UVR exposure and indicator of individual sensitivity to UVR. 14,15 However, the use of visual assessment of erythemal status (ie MED) as a way to estimate UVR exposure has several disadvantages: firstly, it is a subjective and simply phenomenological end point, reflecting acute inflammation with poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies [ 31 , 35 – 37 , 41 , 42 ] assessed use of cardiovascular medications, predominantly statins, with follow-up of up to 48 months, 12 months being the mode. All six studies used either ultrasound or CT to visualise cardiovascular health.…”
Section: Resultsmentioning
confidence: 99%
“…For example, these have assessed the impact of coronary artery calcium screening, but not specifically the role of visualised feedback, and have comprised solely or predominantly observational data, with little randomised evidence [ 28 , 29 ]. Systematic reviews of interventions to increase sun protection behaviours have also been conducted but have typically assessed a wide array of interventions, as opposed to those centred on medical imaging [ 30 , 31 ]. Most pertinently, a Cochrane review of visual feedback of medical images published in 2010 [ 32 ] was unable to reduce uncertainty on this topic due to the limited evidence available at that time, but this has increased greatly since.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is focused on reducing internal UVexposure by using sunscreen. To remove possible barriers such as availability, accessibility, and the costs of sunscreen (10,21,22), we provide sunscreen dispensers placed at easily accessible places. Furthermore, we will electronically monitor the amount of sunscreen used, and provide regular feedback on sunscreen use by means of posters.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study the majority of outdoor workers did use sunscreen during the summer but they used it incorrectly regarding time, frequency and amount applied (21). Additionally, a recently published meta-analysis showed that the most effective intervention for promoting sunscreen use is providing free sunscreen (22).…”
Section: Introductionmentioning
confidence: 99%